2022
DOI: 10.1029/2021wr031549
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Groundwater Level and Soil Moisture Data in an Integrated Land Surface‐Subsurface Model for Southwestern Germany

Abstract: Integrated terrestrial system models predict the coupled water, energy and biogeochemical cycles. Simulations with these models are affected by uncertainties of model parameters, initial and boundary conditions, atmospheric forcings and the biophysical processes. Data assimilation (DA) can quantify and reduce the uncertainty. This has been tested intensively for single compartment models, but far less for integrated models with multiple compartments. We constructed a virtual reality (VR) with a coupled land su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 92 publications
6
17
1
Order By: Relevance
“…In our study, in order to ensure stability and avoid the occurrence of anomalous pressure values in the unsaturated zone related to updating pressure in the DA step, a weakly coupled approach was followed, which implies that only pressure in saturated layers is updated during assimilation. Hung et al (2022) found that the weakly coupled approach outperformed the fully coupled approach for assimilating WTD measurements in TSMP. In the OL run, the vertical division between the unsaturated and saturated zones will differ among ensemble members.…”
Section: Assimilation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, in order to ensure stability and avoid the occurrence of anomalous pressure values in the unsaturated zone related to updating pressure in the DA step, a weakly coupled approach was followed, which implies that only pressure in saturated layers is updated during assimilation. Hung et al (2022) found that the weakly coupled approach outperformed the fully coupled approach for assimilating WTD measurements in TSMP. In the OL run, the vertical division between the unsaturated and saturated zones will differ among ensemble members.…”
Section: Assimilation Methodologymentioning
confidence: 99%
“…TSMP has been applied in a series of studies (e.g., Shrestha et al, 2015;Keune et al, 2016;Furusho-Percot et al, 2019). The combination of PDAF and TSMP has been used for the assimilation of different hydrological variables (e.g., soil moisture and groundwater) at different scales (e.g., hillslope, catchment, and continental scale) (Kurtz et al, 2016;Zhang et al, 2018;Gebler et al, 2019;Naz et al, 2019Naz et al, , 2020Hung et al, 2022). Zhang et al (2018) demonstrated in synthetic experiments with only four grid cells that the joint assimilation of groundwater level and soil moisture data has great potential to improve root zone soil moisture characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, the use of physics-based models has also been pivotal to the success of atmospheric DA in NWP to propagate information to unobserved areas (Kalnay, 2002). At the same time, several studies with current state-of-the-art land surface models also reported limited success (Crow et al, 2020;Hung et al, 2022) in propagating information from one compartment to another, which suggests that the modeling (parameterization) of the coupling and fluxes between land compartments as well as DA strategies need further research.…”
Section: Modelsmentioning
confidence: 99%
“…In addition to improved estimates of the driving forces, as detailed above, an accurate, detailed and spatio-temporal assessment of groundwater fluxes requires also a reliable estimate of soil and aquifer parameters, to avoid errors in parameters leading to over-or underestimation of fluxes. Starting from prior parameter distributions that can be extracted from globally available datasets (e.g., Batjes, 1997;Hengl et al, 2017), data assimilation allows for their dynamic update, which can lead to improved model predictions (e.g., Hung et al, 2022).…”
Section: Earth Observationsmentioning
confidence: 99%